Innovative methods for counteracting pharmaceutical corruption in the preclinical research and clinical trials phase: thesearch for common international standards - Anishchenko, M. A.; Deliya, Y. V.; Filei, Y. V.; Mosaiev, Y. V.; Mykhailyk, O. A.; Аніщенко, Михайло Анатолійович; Михайлик, Олена Анатоліївна (My University, 2020)
The issue of preventing and combating corruption at the stages of preclinical research and clinical trials of medicines is very relevant, because the quality, impartial, objective and reliable research depends on the safety and quality of the investigational medicinal products, and ultimately the lives and health of the large number of patients who will receive these medicinal products.
Keywords: Preclinical Studies; Clinical Trials; Corruption